2003
DOI: 10.1007/s00520-003-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain and its treatment in hospitalized patients with metastatic cancer

Abstract: Pain control in hospitalized cancer patients is not completely satisfactory. The physician's attitude is to underestimate and undertreat pain, while nurses are not adequately trained for timely intervention despite published guidelines for pain management. The findings of this study support the concern of inadequate knowledge and inappropriate attitudes regarding pain management, even in cancer patients hospitalized in medical oncology divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…However, a recent survey taken from 120 consecutive patients in six oncology centers suggests that the medical oncology trend is to underestimate and undertreat pain [4]. We can hypothesize that in Italy there is a gap between what the physicians "know" and what they actually "do" in their daily practice.…”
Section: Discussionmentioning
confidence: 90%
“…However, a recent survey taken from 120 consecutive patients in six oncology centers suggests that the medical oncology trend is to underestimate and undertreat pain [4]. We can hypothesize that in Italy there is a gap between what the physicians "know" and what they actually "do" in their daily practice.…”
Section: Discussionmentioning
confidence: 90%
“…Patients with non-small cell lung cancer undergoing three different protocols of chemotherapy, 82 % of patients had negative PMI scores and were considered poorly managed, according to the class drug-pain intensity ratio [11]. In another Italian survey performed in hospitalized patients, analgesic prescription was found to be inadequate in 43 % of cases [5]. In a large survey performed in Italy about the prevalence of pain and its treatment of a cancer population referring to the majority of oncologic centers, it has been found that about 85 % of patients had their pain uncontrolled, despite receiving opioids [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pain management index (PMI) was calculated to make a historical comparison with previous other epidemiological studies [1,5,9,25], where this tool was used as a surrogate of appropriateness of pain management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the doses of analgesics used were still lower than those generally recommended and more than one third of the physicians were not familiar with the WHO analgesic ladder [5]. Symptoms that impair the quality of life of cancer patients are still underestimated [6] with significant differences in the ratings of the symptoms between the physician and the patient [7,8].…”
Section: Introductionmentioning
confidence: 99%